Legal Pluralism and Rural Welfare: Harmonizing Customary Law and Islamic Principles in Indonesia’s Village Fund Allocation - Iwan Setiajie Anugrah; Andayani Listyawati; Andi Ishak; Niki Elistus Liwaherilla; Ibnu Hasan Muchtar; Fauziah; Suhanah (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Village development is a crucial pillar in achieving national welfare through the effective utilization of the Village Fund. This study aims to analyze the effect of harmonization between customary law and Islamic principles in the utilization of the Village Fund on improving the collective welfare of village communities in Indonesia, especially in Kerinci Regency. The method used is a mixed methods approach, with quantitative techniques through the Partial Least Squares Structural Equation Modeling (PLS-SEM) model and qualitative methods based on in-depth interviews and participatory observation. The results showed that the integration of local cultural values such as gotong royong, normative attachment, and deliberative conflict resolution contributed significantly to strengthening participatory and equitable governance of the Village Fund. In addition, Islamic principles such as deliberation (shura), trustworthiness, justice ('adl), and public good (maslahah 'ammah) provide an ethical basis for decision-making on the use of the Village Fund. The resulting structural model shows high predictive value with support from empirical data, where customary social sanctions act as an effective social control mechanism. The research also found challenges in implementation, such as the dominance of local elites and the lack of contextual understanding of progressive Islamic values. Therefore, recommendations are provided for incorporating the principles of customary and Islamic law into formal village regulations to establish inclusive, equitable, and sustainable development governance. Theoretically, this study enriches the discourse on legal pluralism in village development governance, while practically providing a strategic framework for policymakers and village stakeholders in designing a Village Fund management model oriented towards social justice and sustainability.